EXPERIMENTAL STUDIES OF TRACE-ELEMENT PARTITIONING APPLICABLE TO IGNEOUS PETROGENESIS – SEDONA 16 YEARS LATER - Green T.H. (My University, 1995)
In the 16 years since the Sedona Conference on the behaviour of trace elements in silicate systems, numerous studies providing new data have filled many of the gaps in knowledge of trace-element partitioning evident at that conference. The advent of new microbeam techniques for in situ trace-element analysis has provided great impetus for this work. For example, values for large ion lithophile element (LILE) and high field strength element (HFSE) partitioning between olivine, pyroxene, garnet, amphibole and titanate minerals and silicate liquids have been determined. When plotted on mantle normalizing geochemical diagrams, partition coefficients for the main mantle silicate minerals show steeply inclined patterns (over several orders of magnitude) from LILE to heavy rare-earth elements (HREE). Amphibole, however, has a relatively flat pattern (though still favouring HREE over LILE by about an order of magnitude). Also, there is a notable flattening of the patterns for HREE in pyroxenes and garnet relative to olivine.